1986
DOI: 10.1177/014860718601000103
|View full text |Cite
|
Sign up to set email alerts
|

DRGs and Specialized Nutrition Support. Prospective Payment and Nutritional Support: The Need for Reform

Abstract: The Medicare Prospective Payment System does not recognize the use of parenteral and enteral nutrition services as an explicit factor to be used in determination of DRG payment rates. When the DRGs were originally created, the use of parenteral and enteral nutrition services (PENS) was not coded in discharge data sets. As a result, it was impossible to determine whether patients who received PENS were more expensive to treat. Data we have collected indicate that patients who receive PENS tend to have high hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…These patients are confined to a prolonged course of TPN. It is estimated that over 250,000 patients receive TPN in the United States alone on a yearly basis, 1 resulting in over 11.5 million patient days of care per year. Increasingly, investigators have found that the intestine undergoes significant changes during the administration of TPN with an absence of enteral nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…These patients are confined to a prolonged course of TPN. It is estimated that over 250,000 patients receive TPN in the United States alone on a yearly basis, 1 resulting in over 11.5 million patient days of care per year. Increasingly, investigators have found that the intestine undergoes significant changes during the administration of TPN with an absence of enteral nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital accounting is needed to secure funding for central hospital services such as PN services [39], [40], [41], and the multidisciplinary nutrition support team jointly with the hospital pharmacy should aim at being involved in the evaluation of cost aspects of PN. The nutrition support team should be funded by the health care funds and not by industrial sponsorship to avoid potential conflicts of interests.…”
Section: Cost Aspects Of Pnmentioning
confidence: 99%
“…Since a hospital receives a fixed payment for each patient, some patients will be financial losers for the hospitals. Although a fixed payment system gives providers incentives to undertreat all patients, the more costly patients may be most vulnerable (2). Thus PPS stimulated work on case-mix classification in order to reduce the probability that hospitals would incur losses because of systematic risk and to ensure that the quality of care rendered to specific patients would not be threatened as a result of the classification system.…”
Section: Lavementioning
confidence: 99%
“…These range from studies that essentially describe the structure of PPS (84) to broad sweeping explorations of public policy toward hospitals in which PPS is viewed as an intermediate step between cost-based reimbursement and fully capitated sys tems (38). Studies have been made that analyze the incentives structure embedded in PPS (67,79,81) and that focus on the problems with PPS and recommend policies to ameliorate those problems (2,53).…”
Section: Introductionmentioning
confidence: 99%